Analisis Kemandirian Usaha Mahasiswa dengan Pemanfaatan Teknologi Digital, Inovasi Produk dan Minat Wirausaha - Adi Winarno; Jahju Hartanti (Wahana, 2023)
Prospective entrepreneurs are an important part of developing business independence for students. Student business product innovation is a major force in shaping the ability to develop an interest in entrepreneurship. Entrepreneurship has an important role in improving the economy. Therefore the entrepreneurship education provided in the course aims to foster student entrepreneurial intentions. This study aims to analyze student business independence by utilizing information technology, product innovation and entrepreneurial interest at PGRI Adi Buana University The number of samples in this study were 340 students. Methods of data collection using the questionnaire method. The data collected was analyzed by structural equation modeling using the AMOS 23 application.